2019
DOI: 10.1021/acsomega.9b00581
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight-Fueled, Low-Temperature Ru-Catalyzed Conversion of CO2 and H2 to CH4 with a High Photon-to-Methane Efficiency

Abstract: Methane, which has a high energy storage density and is safely stored and transported in our existing infrastructure, can be produced through conversion of the undesired energy carrier H 2 with CO 2 . Methane production with standard transition-metal catalysts requires high-temperature activation (300–500 °C). Alternatively, semiconductor metal oxide photocatalysts can be used, but they require high-intensity UV light. Here, we report a Ru metal catalyst that facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 40 publications
2
41
0
Order By: Relevance
“…Also our group demonstrated an efficient sunlight-powered Sabatier reaction, driven by the LSPR of alumina-supported Ru nanorods. [12] We have demonstrated that individual Ru nanorods efficiently harvest sunlight based on their broadband LSPR. For this Ru nanorod catalyst, we identified a large 'nonthermal' contribution at a slightly elevated sunlight intensity of 8.5 kW m À 2 (8.5 sun), resulting in a high photon-to-methane conversion efficiency (PTM) of 55 % [12] over the whole solar spectrum.…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…Also our group demonstrated an efficient sunlight-powered Sabatier reaction, driven by the LSPR of alumina-supported Ru nanorods. [12] We have demonstrated that individual Ru nanorods efficiently harvest sunlight based on their broadband LSPR. For this Ru nanorod catalyst, we identified a large 'nonthermal' contribution at a slightly elevated sunlight intensity of 8.5 kW m À 2 (8.5 sun), resulting in a high photon-to-methane conversion efficiency (PTM) of 55 % [12] over the whole solar spectrum.…”
mentioning
confidence: 96%
“…The PTM is the quotient of the increase in reaction rate upon illumination and the rate of incident photons. [12] It carries the same definition as the so-called 'apparent quantum yield' introduced by Liu and coworkers, [7] and quantifies the 'nonthermal' share of the reaction. In contrast to nanorods, the LSPR of spheroidal Ru nanoparticles is positioned in the UV.…”
mentioning
confidence: 99%
See 3 more Smart Citations